The impact of the method of presenting instructions of postoperative care on the quality of life after simple tooth extraction - Yaser Abdulaziz M. Alsahafi; Albraa Badr Alolayan; Wejdan Alraddadi; Amna Alamri; Maryam Aljadani; Meshal Alenazi; Shadia Abdel-Hameed Elsayed (Wolters Kluwer Medknow Publications, 2021)
Introduction: The extraction of teeth is a common dental treatment. Healing complications have been reported to be influenced by patients' knowledge and compliance with postoperative instructions. Aim : The goal of the study was to define the influence of the way postoperative instructions delivering method on reducing morbidity and problems experienced after simple tooth extraction. Materials and Methods: A single-blind randomized clinical trial was designed at clinics of Oral Maxillofacial Surgery, Taibah University. Patients were distributed to two classes on a random basis. The first group was provided only with verbal instructions (VI) after dental extraction. The second group was given written and verbal (CVWI) instructions. Postoperative pain, swelling, sleep impairment, oral functions, and general activity were reported using an assessment tool for oral health life quality (OHQ). Results and Discussion: The mean OHQ scores were 14.28 ± 6.36 for VI and 13.46 ± 5.78 for CVWI, which did not indicate a statistical difference (P = 0.50). Of the 100 participants, 51% were mildly affected, whereas 22% were severely affected. Females constituted 51% of the study participants. There was a statistically significant difference between females' mean score values compared to males (15.78 ± 4.5-11.88 ± 6.5) with P = 0.001. About 56% of the participants were nonSaudis and 33% hold a high-school diploma. Conclusions : There was no difference between the two approaches used to present the postoperative instruction in the postextraction OHQ. Following tooth extraction, female patients experience a significantly greater decline in their OHQ. Translation of written postoperative instructions in more than one language should be available in our institution to improve OHQ during the postextraction period.